Source code China : the new global hub of IT outsourcing - Eltschinger, Cyrill, 1965- (John Wiley & Sons, 2007)
Source Code China: The New Global Hub of IT Outsourcing explores the new, uncharted, and potentially profitable, waters of IT outsourcing in China.